2005
DOI: 10.1146/annurev.physiol.67.040403.101353
|View full text |Cite
|
Sign up to set email alerts
|

A Physiological View of the Primary Cilium

Abstract: The primary cilium, an organelle largely ignored by physiologists, functions both as a mechano-sensor and a chemo-sensor in renal tubular epithelia. This forgotten structure is critically involved in the determination of left-right sidedness during development and is a key factor in the development of polycystic kidney disease, as well as a number of other abnormalities. This review provides an update of our current understanding about the function of primary cilia. Much new information obtained in the past fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
202
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(203 citation statements)
references
References 62 publications
1
202
0
Order By: Relevance
“…This phenomenon has received much attention as it was hypothesised that an absence of flow sensing in renal epithelia causes polycystic kidney disease [133]. Intriguingly, the flow-induced release of ATP from endothelial cells and the flowstimulated increase of [Ca 2+ ] i in renal epithelia show striking similarities: They are transient, gradable by the amount of applied shear stress, cause refractoriness to subsequent stimuli and are inhibited by removal of extracellular Ca 2+ [127,134]. Recently, it was shown that the flow-induced [Ca 2+ ] i increase in intact renal tubules was caused by released nucleotides and stimulation of P2Y 2 receptors [124].…”
Section: Mechanically Released Nucleotidesmentioning
confidence: 99%
“…This phenomenon has received much attention as it was hypothesised that an absence of flow sensing in renal epithelia causes polycystic kidney disease [133]. Intriguingly, the flow-induced release of ATP from endothelial cells and the flowstimulated increase of [Ca 2+ ] i in renal epithelia show striking similarities: They are transient, gradable by the amount of applied shear stress, cause refractoriness to subsequent stimuli and are inhibited by removal of extracellular Ca 2+ [127,134]. Recently, it was shown that the flow-induced [Ca 2+ ] i increase in intact renal tubules was caused by released nucleotides and stimulation of P2Y 2 receptors [124].…”
Section: Mechanically Released Nucleotidesmentioning
confidence: 99%
“…Medical students are most familiar with the multiple, motile cilia on the cells that line the lumens of ducts in several tissues, but many cilia are nonmotile and are present just one per cell. [1][2][3] Cilia play obvious roles in several tissues, including cell motility (sperm) and transport of mucus, other fluids, and even other cells (oviduct and efferent ducts of the testis). Less well appreciated are the roles of cilia in allowing us to experience our environment.…”
Section: A Cilium On (Almost) Every Cellmentioning
confidence: 99%
“…liver; ADP; adenylyl cyclases; cAMP; protein kinase A; exchange protein directly activated by cAMP; A-kinase anchoring protein 150 CHOLANGIOCYTES, the epithelial cells lining intrahepatic bile ducts (IBDs), contain primary cilia, nonmotile, solitary organelles extending from the apical plasma membrane into the ductal lumen (21,28,29). In many cell types, including cholangiocytes, primary cilia function as sensory organelles detecting multiple (i.e., mechano-, osmo-, chemo-) stimuli and transducing them into intracellular signaling (12,16,27,40,46). However, although increasing evidence suggests the ability of primary cilia to act as mechano-and osmosensors (16, 24, 28, 34 -37, 40 -42, 49, 50, 55), less data support their chemosensory functions.…”
mentioning
confidence: 99%
“…In many cell types, including cholangiocytes, primary cilia function as sensory organelles detecting multiple (i.e., mechano-, osmo-, chemo-) stimuli and transducing them into intracellular signaling (12,16,27,40,46). However, although increasing evidence suggests the ability of primary cilia to act as mechano-and osmosensors (16, 24, 28, 34 -37, 40 -42, 49, 50, 55), less data support their chemosensory functions.…”
mentioning
confidence: 99%